Sosialisasi Penerapan Kontekstual Konsep Matematika dalam Ibadah Salat di SMP Ibnu Khaldun, Banda Aceh: Socialization of the contextual application of mathematical concepts in prayer services at Ibnu Khaldun Middle School, Banda Aceh - Nazariah, Nazariah; Yusliani, Hamdi; Helmanda, Cut Mawar (LP2M INSURI Ponorogo, 2024)
Prayer can serve as a valuable component of mathematical education, especially in Islamic schools, based on the constructivist learning theory. Utilizing community-based research methods, such as action and participatory research, fosters self-awareness and conflict resolution. Through prayer, students can engage in mathematical concepts like counting and multiplication by observing actions like bows and prostrations. Media supplements, such as a ball count, can enhance learning. Contextual notions of school mathematics are evident in prayer, such as adding and multiplying natural numbers, understanding sets, arithmetic sequences, and geometry concepts like lines, angles, and parallelism. For instance, the number of prayer units illustrates adding natural numbers, while the tahajjud prayer exemplifies multiples of two. Moreover, the congregation's rows during group prayer demonstrate line segments and parallel lines, while the standing position showcases various angles. These connections highlight the relationship between prayer and mathematics, offering unique insights into both disciplines. Integrating prayer into mathematical education not only enriches students' understanding but also fosters a holistic approach to learning.